Modelo para la identificación de perfiles motivacionales y aplicación de incentivos eficientes en el ámbito organizacional - Nicolás Carminatti; Lucas Canga (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2022)
– Based on the theory of personality BIS / BAS (Carver and White, 1994) and the motivational theory of Self-determination theory (Gagné and Deci, 2005), studied the relationship between both models in order to identify profiles that allow us to understand the characteristics and motivational needs of individuals. A sample of 232 individuals was taken from whom the complete BIS/BAS questionnaire, the complete questionnaire of the Multidimensional Work Motivation Scale (Gagné et al., 2015) was carried out and a series of incentives were investigated with the objective of having the most effective for each profile. The five proposed profiles allow us to understand how the motivation subtypes behave within the BIS/BAS personality model and how the most effective set of incentives for each profile is composed.
Keywords: 330; Motivación; incentivos; personalidad; neuromotivación; neuroliderazgo; organización; management; BIS/BAS; self determination theory.; amenazas sociales; recompensassociales; SIC; SAC; SCARF; satisfacción laboral; clima laboral; engagement; dolor social; compromiso organizacional; Motivation; incentives; personality; neuromotivation; neuroleadership; organization; management; BIS/BAS; self determination theory.; social threats; social rewards; SIC; SAC; SCARF; job satisfaction; work environment; engagement; social pain; organizational commitment